Analysis Of Incompleteness In Filling In The Discharge Summary Of Inpatients At Lawang Medika Hospital, Malang District, East Java Province - Laili Wulandari; Tiara Kelana Zahrotunnisa (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2025)
The discharge summary form has an important function for the claim process and further treatment needed by patients in the hospital. The form contains information about the patient's condition from admission to discharge and the patient's follow-up treatment plan. The purpose of this field learning practice is to analyze the causes of incomplete discharge contents for inpatients at Lawang Medika Hospital, Malang Regency, East Java Province using Fishbone diagrams; Urgency, Seriousness, and Growth analysis; and SWOT analysis. Identifying problems using Fishbone diagrams, determine problem solving priorities using Urgency, Seriousness, and Growth analysis; and plan interventions by identifying strategies using SWOT.: Several factors influence the incompleteness of the discharge summary are man, money, method, machine and materials. Due to these factors, priority problems can be determined that must be resolved, so the results obtained are delays in providing forms, there is no SOP for filling out discharge summaries and has not been socialized to officers. To solve this problem, it can be solved with an aggressive strategy obtained from analysis results and SWOT diagrams. The strategy that must be implemented in this condition is to support aggressive growth policies (Growth Oriented Strategy). The hospital can solve problems according to the factors and prioritize problems that must be resolved so as not to hamper the function of the discharge summary